Aspek Ekologi Budaya dalam Kumpulan Puisi Odong-Odong Fort De Kock Karya Deddy Arsya - Melia, Gusmi; Bahardur, Iswadi; Armet, Armet (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research aims to determine aspects of cultural ecology in literary works contained in the poetry collection Odong-Odong Fort De Kock by Deddy Arsya, seen from the perspective of literary ecocriticism. The aim of this research is to describe the cultural ecology depicted in the poetry collection Odong-Odong Fort De Kock by Deddy Arsya. This type of research is qualitative research with descriptive analysis methods. The data in this research are excerpts from lines contained in the poetry collection Odong-Odong Fort De Kock by Deddy Arsya which contains aspects of literary ecology. The data source in this research is the poetry collection Odong-Odong Fort De Kock by Deddy Arsya. Based on the analysis of related data, it can be concluded that there are three basic things in cultural ecology. First, the relationship between technology, production or exploitation of resources and the environment. Second, the community's pattern of action in exploiting and producing resources using the technology they have. Third, behavioral patterns in society that influence other cultural aspects such as value systems, belief systems and religious systems.